2016
DOI: 10.2147/ijn.s104774
|View full text |Cite
|
Sign up to set email alerts
|

Phytosome-hyaluronic acid systems for ocular delivery of L-carnosine

Abstract: This study reports on L-carnosine phytosomes as an alternative for the prodrug N-acetyl-L-carnosine as a novel delivery system to the lens. L-carnosine was loaded into lipid-based phytosomes and hyaluronic acid (HA)-dispersed phytosomes. L-carnosine-phospholipid complexes (PC) of different molar ratios, 1:1 and 1:2, were prepared by the solvent evaporation method. These complexes were characterized with thermal and spectral analyses. PC were dispersed in either phosphate buffered saline pH 7.4 or HA (0.1% w/v)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…NAC IR spectra showed a distinctive vibrational type of peaks (Figure c) in the region with elevated frequency including an expansion vibration at 3,237 and 3,049 cm −1 for the –CON–H (amide hydrogen) and NH3+ (protonated terminal amine) related to free l ‐carnosine, respectively. However, other remarkable peaks were recognized at 2,162 and 1,643 cm −1 that are caused by the N–H vibrational bending of amide group and imidazole stretching sequentially (Abdelkader et al, ). In the FT‐IR spectra of CIP nanosponges or its binary mixture with NAC, it was observed that the characteristic peaks of Cipro and/or NAC in the fingerprint region, that is, 3,524, 3,237, and 3,049 cm −1 were masked and cannot be distinguished from that of HPβ‐CD to appear as a single broad peak suggesting definite interactions between drugs and nanosponges (Swaminathan et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NAC IR spectra showed a distinctive vibrational type of peaks (Figure c) in the region with elevated frequency including an expansion vibration at 3,237 and 3,049 cm −1 for the –CON–H (amide hydrogen) and NH3+ (protonated terminal amine) related to free l ‐carnosine, respectively. However, other remarkable peaks were recognized at 2,162 and 1,643 cm −1 that are caused by the N–H vibrational bending of amide group and imidazole stretching sequentially (Abdelkader et al, ). In the FT‐IR spectra of CIP nanosponges or its binary mixture with NAC, it was observed that the characteristic peaks of Cipro and/or NAC in the fingerprint region, that is, 3,524, 3,237, and 3,049 cm −1 were masked and cannot be distinguished from that of HPβ‐CD to appear as a single broad peak suggesting definite interactions between drugs and nanosponges (Swaminathan et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…CIP showed sharp peaks at diffraction angles of 12, 20, and 27° suggesting its crystalline nature (Mallikarjuna et al, ; Sahoo, Chakraborti, & Mishra, ). Within this pursue, NAC was considered as a typical high crystallinity drug, due to its sharp X‐ray peaks, where at 20, 22.8, and 25° diffractive angles, the main distinctive peaks of NAC were revealed (Abdelkader et al, ). A comparative analysis of diffractograms of individual components and nanosponge formulations showed that the diffractograms of nanosponge formulations (C1, C2, C5, CA5, and CA6) are almost identical to that of HPβ‐CD, and it is hard to distinguish the characteristic crystallinity peaks of the pure drugs.…”
Section: Resultsmentioning
confidence: 99%
“…The prepared phytosome using sinigrin shows higher efficiency than control to release the compound in a slow and controlled manner into the stratum corneum for wound healing [51]. Abdelkader et al formulated L-carnosine phytosome by combining hydrogel and lipid-based carrier which shows sustained drug pervasion and inhibits the browning of the lens and protects from cataract formation [52]. Damle et al focused on encapsulating orange peel and liquorice extracts into phospholipid complex which exhibited as a better topical dosage delivery towards skin that ensured high cutaneous absorption of phytoconstituents in the skin for long period of action in contradiction to skin ageing [53].…”
Section: Phytosomementioning
confidence: 99%
“…Hyaluronic acid phytosomes loaded with L-carnosine was prepared by Abdelkader et al [44] in different molar ratios by solvent evaporation technique, where the prepared phytosomes showed ex vivo transcorneal permeation of L-carnosine loaded phytosome without affecting human corneal cell viability.…”
Section: In Vivo Evaluationmentioning
confidence: 99%